Gambaran Tingkat Pengetahuan Ibu Hamil tentang Pencegahan Preeklamsia - Siti Sofia; Firdawsyi Nuzula; Haswita Haswita (Akademi Kesehatan Rustida, 2021)
Pre-eclampsia is a disease with the signs of hypertension, proteinuria, and edema arising from pregnancy. There are 20 maternal mortality rates in Banyuwangi, most of the causes of maternal mortality are PEB / Eclampsia as many as 5 people (25%). This study aims to describe the level of knowledge of pregnant women about the prevention of preeclampsia in the Kalibaru Kulon Public Health Center Banyuwangi. This study uses a quantitative descriptive method. The variable in this study was the knowledge of pregnant women about the prevention of preeclampsia. The population in this study were 58 pregnant women who continued to visit every month at the Kalibaru Kulon Public Health Center Banyuwangi. The sampling technique used was accidental sampling, while the sample obtained in June 2020 was 37 samples. Data collection techniques using a questionnaire.The results of this study indicate that the level of knowledge of pregnant women about the prevention of preeclampsia in the Kalibaru Kulon Banyuwangi Health Center in 2020 is categorized as good as many as 35 people (95%). where respondents are knowledgeable, aged 21-40 years, elementary school education, work as a housekeeper and the number of parity> 2. It is advisable for pregnant women to be more active in seeking health information, especially about the prevention of preeclampsia in order to increase knowledge so that they can prevent and avoid unwanted things.